Pengukuran Efektivitas Kinerja Koperasi Karyawan PT X Berdasarkan Rasio Aktivitas - . Basuki (JURNAL CITRA WIDYA EDUKASI, 2020)
The purpose of this research is to measure the level of efficiency of the resources owned in an effort to generate sales based on the ratio of activities. The activity ratio is the ratio used to assess the company's ability to carry out its daily activities. The research was conducted at Koperasi Karyawan PT X - Bekasi. The sample used is balance sheet data from 2016 to 2019. Measurement of activity ratios uses five parameters, ie: accounts receivable turnover, inventory turnover, working capital turnover, fixed asset turnover and total asset turnover. The result of reserach is that based on the data for the last four years, the average turnover of accounts receivable for 38.1 days is classified as less effective, the average inventory turnover for 12.32 days is classified as effective, the average turnover of working capital is 7 times as ineffective, the average fixed asset turnover was 111.2 times which was classified as effective and the average total asset turnover was 0.23 times which was classified as less effective.